1950
DOI: 10.1039/jr9500002400
|View full text |Cite
|
Sign up to set email alerts
|

493. Kinetics and mechanism of aromatic nitration. Part II. Nitration by the nitronium ion, NO2 +, derived from nitric acid

Abstract: The plan underlying the investigation as developed in this collection of papers, which includes papers of several concurrent series, is explained. The series to which this paper belongs is concerned with the kinetics and products of aromatic nitration. The other series deal with various kinds of physical and synthetical evidence, all bearing directly or indirectly on the subject of nitration. In this paper the kinetics of aromatic nitration by nitric acid are considered. The treatment is divided into Sections,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
59
0
2

Year Published

1978
1978
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 1 publication
2
59
0
2
Order By: Relevance
“…It is highly likely that with toluene at these high acid concentrations k3' >> k-,' and formation of the encounter complex (reaction 2) is rate controlling when the nitration rate is first order in toluene (13 ' (15). With these it is likely that k-,' >> k,' and [3] I is rate controlling, so that k2 = (kl'aH+/k-laH20) (k,'/k-,')k,' and E, = A H , + AH, + E,', AH, ' being the heat of reaction 2, the formation of the encounter complex. One expects AH, to be small and , E,' to be relatively independent of the medium.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is highly likely that with toluene at these high acid concentrations k3' >> k-,' and formation of the encounter complex (reaction 2) is rate controlling when the nitration rate is first order in toluene (13 ' (15). With these it is likely that k-,' >> k,' and [3] I is rate controlling, so that k2 = (kl'aH+/k-laH20) (k,'/k-,')k,' and E, = A H , + AH, + E,', AH, ' being the heat of reaction 2, the formation of the encounter complex. One expects AH, to be small and , E,' to be relatively independent of the medium.…”
Section: Resultsmentioning
confidence: 99%
“…where k, = k,' aH+ and When k2[ArH] >> k , , [4] simplifies to which accounts for the rate being zero order with respect to the aromatic substrate under certain conditions such as those that often occur in organic solvents (2)(3)(4)(5). O n the other hand whenk, >> k, [ArH], [4] simplifies to which accounts for the rate being first order with respect to the aromatic substrate under other conditions such as those which normally obtain in aqueous sulphuric acid.…”
Section: Introductionmentioning
confidence: 99%
“…This work aims to bring about a detailed understanding of the two gasphase reactions in Equations (1) and (2) through the combined application of experimental techniques and a detailed ab initio study at the MP2/6 ± 31 G* level of theory. In particular, we report new theoretical and experimental results for the reaction in Equation (1), whereas for the reaction in Equation (2) we use both earlier experimental and theoretical results [7,8] and new results that allow us to perform a more comprehensive comparative analysis of the two reactions. We have found that the two reactions are mechanistically very similar and that they proceed mainly according to a 1,3-dipolar-type addition.…”
Section: Introductionmentioning
confidence: 96%
“…We have found that the two reactions are mechanistically very similar and that they proceed mainly according to a 1,3-dipolar-type addition. This reaction leads to the formation of two structurally related end products, nitrosated ketene from the reaction in Equation (1) and nitrosated acetaldehyde from the reaction in Equation (2).…”
Section: Introductionmentioning
confidence: 98%
“…The organic reactant (i.e., benzene or toluene) is transferred into the aqueous phase, also called mixed acid, where it reacts with the nitronium ion formed from the nitric acid. The sulphuric acid acts as a catalyst [1,2]. The strength of the sulphuric acid used determines the type of reaction developed, enabling operation in the kinetic or the fast reaction regimes, if the remaining parameters are kept constant [3].…”
Section: Introductionmentioning
confidence: 99%